Prevalence of stunting and determinants of growth failure in children with Type 1 diabetes - Bhor, Shital; Oza, Chirantap; Khadilkar , Anuradha; Ladkat, Dipali; Gondhalekar, Ketan; Khadilkar, Vaman (Indian Journal of Child Health, 2022)
Objectives: India is home to the highest number of prevalent cases of Type-1 diabetes (T1D) in children. There is scarcity of data on the growth failure of children with diabetes, especially those having complications and comorbidities, thus, we conducted this study with the objective to determine the prevalence and predictors of stunting in children with T1D. Methods: This cross-sectional study included 350 children and adolescents aged 1–18 years with T1D. Demographic data, anthropometry, diet, sexual maturity rating, and biochemical measurements were performed using standard protocols. Short stature was defined as height for age Z-score